2006
DOI: 10.1016/j.cell.2006.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Origin of a Bipotential Myocardial and Smooth Muscle Cell Precursor in the Mammalian Heart

Abstract: Despite recent advances in delineating the mechanisms involved in cardiogenesis, cellular lineage specification remains incompletely understood. To explore the relationship between developmental fate and potential, we isolated a cardiac-specific Nkx2.5(+) cell population from the developing mouse embryo. The majority of these cells differentiated into cardiomyocytes and conduction system cells. Some, surprisingly, adopted a smooth muscle fate. To address the clonal origin of these lineages, we isolated Nkx2.5(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
524
1
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 496 publications
(568 citation statements)
references
References 36 publications
32
524
1
11
Order By: Relevance
“…Eomes overexpression also promoted the appearance of endothelial cells (expressing VE-cadherin and CD31; Fig 1D,E,J) and smooth muscle cells (expressing smooth muscle actin; Fig 1F,G,K and supplementary Fig S2B online). Altogether, the three types of cells derived from multipotent cardiovascular progenitors (MCPs) [27,[35][36][37] were massively increased following Eomes expression in DDM, although we cannot rule out that some endothelial and smooth muscle cells could also derive from other progenitors (such as the hemangioblasts [38] that could also be induced following Eomes expression). We and others have recently demonstrated that a combination of monoclonal antibodies (Flk1/Pdgfra) can be used to isolate the earliest Mesp1 expressing MCPs arising during ESC differentiation [16,27].…”
Section: Results and Discussion Eomes Promotes Cardiogenesis In Escmentioning
confidence: 99%
“…Eomes overexpression also promoted the appearance of endothelial cells (expressing VE-cadherin and CD31; Fig 1D,E,J) and smooth muscle cells (expressing smooth muscle actin; Fig 1F,G,K and supplementary Fig S2B online). Altogether, the three types of cells derived from multipotent cardiovascular progenitors (MCPs) [27,[35][36][37] were massively increased following Eomes expression in DDM, although we cannot rule out that some endothelial and smooth muscle cells could also derive from other progenitors (such as the hemangioblasts [38] that could also be induced following Eomes expression). We and others have recently demonstrated that a combination of monoclonal antibodies (Flk1/Pdgfra) can be used to isolate the earliest Mesp1 expressing MCPs arising during ESC differentiation [16,27].…”
Section: Results and Discussion Eomes Promotes Cardiogenesis In Escmentioning
confidence: 99%
“…Using the same markers as to isolate the different MCPs during embryonic de velopment, mouse and human bipotent and tripotent MCPs have been isolated during ESC differentiation, giving rise to CMs, SMCs, and ECs similar to their in vivo potential (Kattman et al, 2006;Moretti et al, 2006;Wu et al, 2006;Yang et al, 2008;Bu et al, 2009). The spontaneous appearance of cardiovascular cells during the differentiation of ESCs has created great enthu siasm among developmental biologists for studying, using reductionist in vitro approaches, the complex cellular and mo lecular mechanisms governing cardiovascular differentiation and cardiovascular diseases as well as providing a means of generating cardiovascular cells for cellular therapy and drug or toxicity screening (Murry and Keller, 2008).…”
Section: Mesp1-gfp-expressing Cells Represent the Earliest Source Of mentioning
confidence: 99%
“…Random labeling of cardiac precursors during em bryonic development also revealed the existence of rare clones that contributed to both FHF and SHF lineages and that could repre sent a common cardiovascular progenitor for both heart fields (Meilhac et al, 2004). Recent studies showed that, during mouse embryonic development, tripotent MCPs that are able to differen tiate at the clonal level into CMs, SMCs, and ECs can be marked and isolated based on Brachyury (Bry) and Flk1 (Kattman et al, 2006) or Isl1 and Flk1 expression (Moretti et al, 2006), whereas bipotent MCPs that give rise to CM and SMC lineages can be iso lated based on Nkx2-5 and c Kit expression (Wu et al, 2006). These studies demonstrated that cardiac cells arise from the differ entiation of multipotent progenitors, with the ability to differenti ate at the clonal level into the different cardiovascular lineages (Kattman et al, 2006;Moretti et al, 2006;Wu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, culturing of vascular smooth muscle cells has been reported to possibly cause a loss in the expression of P2X 1 receptors [30,31]. Moreover, coronary smooth muscle cells and myocardial cells are likely to be derived from a common precursor cell [32], suggesting potential differences of coronary smooth muscle on the one hand and noncoronary vascular smooth muscle on the other hand. Therefore, we now examined the effects of α,β-methylene-ATP and its analog β,γ-methylene-ATP on the proliferation of human coronary smooth muscle cells cultured under conditions suitable to maintain the contractile smooth muscle phenotype [20,25].…”
Section: Introductionmentioning
confidence: 99%